Making the right investment choice? comparing the performance between Islamic and conventional equity unit trust funds in Malaysia - Othman, Anwar Hasan Abdullah; Aziz, Hasanuddeen Abdul; Kassim, Salina (IIUM Institute of Islamic Banking and Finance (IIiBF), 2019)
In a dual capital market system such as in Malaysia, the possibility for investors to choose either the Islamic funds or the conventional funds is highly likely depending on the performance of the funds. While some investors would adhere to the requirements of the Sharīʿah in making their investment decision, there remains many who are guided purely by profit and would likely switch depending on the fund performance. This study is carried-out to compare the performance of both the Islamic and conventional equity unit trust funds in Malaysia in order to guide investors in planning their choice and determining their portfolio diversification strategy. The two-sample test of hypothesis was conducted to compare the performance of the two population means via the capital gain over the period from January 2004 to December 2009. The findings of this study show that the Islamic equity unit trust funds perform better than the conventional equity unit trust funds in the Malaysian capital market during the specified time period, suggesting that the Islamic equity unit trust funds in Malaysia are more profitable than the conventional equity unit trust funds. This study provides relevant inputs to further support the development of a vibrant Islamic equity market could serve as an international Islamic financial hub at the global level.